2002
DOI: 10.1002/jlcr.631
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 14C‐labeled 4‐hydroxyindole as an intermediate for the preparation of (S)‐2‐[4‐[2‐[3‐(indol‐2‐[14C]‐4‐yloxy)‐2‐hydroxypropylamino]‐2‐methylpropyl]‐phenoxy]pyridine‐5‐carboxamide (LY368842‐[indole‐14C]) glycolate

Abstract: Synthesis of 4‐hydroxyindole labeled with 14C at the 2‐position was accomplished based on the vicarious nucleophilic substitution reaction of benzyl‐protected 3‐nitrophenol with p‐chlorophenoxyacetonitrile‐[1‐14C]. This was followed by the reductive cyclization of o‐nitrocyanomethyl derivative by palladium catalyzed hydrogenation. p‐Chlorophenoxyacetonitrile‐[1‐14C] was prepared from commercially available p‐chlorophenoxymethyl chloride and sodium cyanide‐[14C]. 4‐Hydroxyindole‐[2‐14C] was used for the synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…This protocol was recently applied to the synthesis of 4-hydroxyindole labeled with 14 C at the 2-position, the key intermediate for the synthesis of 14 C-labeled β 3 adrenergic agonist LY368842 (Scheme 102) . The required chlorophenoxyacetonitrile was prepared from commercially available 4-chlorophenoxymethyl chloride and K 14 CN.…”
Section: Syntheses Of Heterocyclic Systemsmentioning
confidence: 99%
“…This protocol was recently applied to the synthesis of 4-hydroxyindole labeled with 14 C at the 2-position, the key intermediate for the synthesis of 14 C-labeled β 3 adrenergic agonist LY368842 (Scheme 102) . The required chlorophenoxyacetonitrile was prepared from commercially available 4-chlorophenoxymethyl chloride and K 14 CN.…”
Section: Syntheses Of Heterocyclic Systemsmentioning
confidence: 99%
“…The use of a transfer hydrogenation procedure appeared to be much faster compared to direct reduction with hydrogen over palladium or other types of catalysts. Indeed, there were a number of reports of intramolecular nitrile-mediated reductive alkylations that have been conducted with hydrogen as a reductant at various pressures and over various types of catalysts. Also, using active rhodium catalysts, Galan et al have demonstrated direct reductive coupling of aliphatic nitriles to form the corresponding secondary amines in high yield. In these instances, direct reduction of nitrile led to the corresponding amine, which then reacted with nitrile leading to a secondary amine product in a process likely identical to that reported here.…”
mentioning
confidence: 99%
“…It was also evident that conditions that favored a high ratio of We next set out to investigate the effect of basicity on ORCY and radiolabeled product distribution. The results listed in Table 1, entries 5 and 6 showed that no [ 11 Increasing the pH to 8.7 increased the ORCY to 60% but only We initially tested several reducing agents for the reductive cyclization of [ 11 C]-2 to [2-11 C]indole including: Pd-C/H 2 in ethyl acetate 22,23 and in alcoholic solvents; 24,25 Pd-C/H 2 in ethanol/acetic acid; 9,26,27 Pd-C in the presence of in situ H 2 ; 28,29 RANEY® Nickel or Pd-C in the presence of NH 4 CO 2 H/ HCO 2 H; 30 Al-NiCl 2 •6H 2 O; 31 Zn/acetic acid. 32 Results were generally disappointing: although most worked under carrieradded conditions with or without carbon-11, they either provided only a trace of desired [2-11 C]indole or none at all under no-carrier-added (NCA) conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In 2002, Czeskis and colleagues reported an elegant method for synthesis of 4-hydroxy [2-14 C]indole. 9 Starting from Na 14 CN, they first synthesized p-chlorophenoxy [1- 14 C]acetonitrile which was reacted with benzyl-protected 3-nitrophenol via a vicarious nucleophilic substitution reaction to afford a 2-(2-nitrophenyl) acetonitrile derivative, which was reduced and cyclized to form 14 C-labeled 4-hydroxyindole. Four years later, Pedras and Okinyo reported a synthesis of stable isotope deuterium labeled [5,6,7,8-2 H 4 ]indole using chloroacetonitrile direct alkylation and reductive cyclization reactions.…”
mentioning
confidence: 99%